Food subsidy changes in Sri Lanka: The short-run effect on the poor - Edirisinghe, Neville (International Food Policy Research Institute, 1988)
When a basic needs approach began to be emphasized in development economics, Sri Lanka gained much prominence due to its long-standing involvement in broad social welfare policies.1 Long before the advent of the basic needs approach, Sri Lanka had pursued a policy of allocating large amounts of resources to enhancing the health, education, and nutrition of the population. On the other hand, it was not too long after the virtues of meeting basic needs started to be appreciated globally that Sri Lanka made a sharp turn from welfare through sharing of poverty to welfare through growth. The change that began in 1977 has led to abandonment of the major element in welfare policy that aimed at broad nutritional welfare through food subsidies. Operationally, the change has resulted in the elimination of all rationing and price subsidies on food and the introduction of an income transfer program through issuance of food stamps intended to protect the really needy. Implicit in the curtailed welfare policies is the expectation that newly adopted growth-oriented investment policies will generate incomes for all, including the present poor. This chapter will examine some implications of this change on fiscal costs, income distribution, and the nutritional welfare of low-income households.